In Vivo Wound Healing Effect of Water Extract of Stereospernum kunthianum Stem-Bark - Tsala, David Emery; Joseph, Mendimi Nkodo; Heroyine, Lissia Toussoumna; Solomon, Habtemariam (Journal of Medicinal Herbs and Ethnomedicine, 2016)
The objective of the present study was to evaluate the in vivo wound healing effect of water extract of Stereospernum kunthianum-bark. The plant is mainly used by the local people of Mayo-Danay, Cameron as wound healing agent. The healing activity was evaluatedin rats using excision and incision wound on normal dexamethasone-delayed wound healing. Control animals received normal saline topically while other groups received dexamethasone (i.m), water extract orally or dexamethasone with the plant extract. The extract treated wounds were found to epithelize faster than those of controls dexamethasone-treated rats. Significant increase in skin tensile strength was observed in earlier than in later groups. Histological examination of incision wounds of extract-treated group showed dense collagen cross-linking and numerous blood vessels. The present study concludes that the stem bark of Stereospernum kunthianum possesses excellent wound healing potential that may substantiate its use in the traditional medicine.